Traditional chinese medicine in coronary microvascular disease - Yang, Zhihua; Lin, Shanshan; Liu, Yangxi; Ren, Qiuan; Ge, Zhao; Wang, Ci; Bi, Yingfei; Wang, Xianliang; Mao, Jingyuan (Frontiers in Pharmacology, 2022)
Coronary microvascular disease (CMVD) is common in patients with cardiovascular risk factors and is associated with an increased risk of adverse cardiovascular events. Although the study of CMVD in modern medicine is ongoing, there is still no effective treatment for it. Traditional Chinese medicine (TCM) has some clinical advantages based on syndrome differentiation and individualized treatment. In this review, we review the clinical significance, pathogenesis, and current treatments of CMVD and systematically summarize the clinical efficacy and potential action mechanisms of TCM for CMVD. In addition, the scientific problems that need to be solved urgently and the research strategy of TCM for CMVD are described. CMVD has great clinical significance, but there are still many gaps in the related research. This review aims to attract the attention of clinicians to CMVD and promote research on CMVD in TCM.